Use of laryngeal mask airway in paediatric external dacrocystorhinostomy surgery under anaesthesia: a retrospective study - Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Many recent studies have shown the use of Laryngeal Mask Airway (LMA) in Adenotonsillectomy but not in Dacryocystorhinostomy (DCR) surgery in paediatric age group. So, this study was carried out to evaluate the safety of LMA use in Pediatric External Dacryocystorhinostomy performed under General Anaesthesia. MATERIAL AND METHOD:This retrospective study was carried out by collecting the data of 96 children with American Society of Anesthesiologists (ASA) physical status 1 from Lumbini Eye Institute (Memorandum of Understanding with UCMS), Bhairahawa, Nepal from September 2008 to June 2014 to find out any significant cardio-respiratory complications associated with the use of LMA. RESULTS: This study found no significant cardio-respiratory complications during insertion and after removal of LMA. Though airway obstruction and laryngospasm had occurred in few children, it was easily managed by bag and mask ventilation. Time taken to shift the patients from Operation Theatre to Post Anaesthesia Care Unit (PACU) was also less, average 13 minutes. CONCLUSION: This study showed that LMA can safely be used in children undergoing External Dacryocystorhinostomy under general anesthesia with the use of intermittent suctioning and without any interruption in surgery.